2021
DOI: 10.3390/cancers13164044
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival after Breast-Conserving Therapy Compared with Mastectomy in Stage I-IIA Breast Cancer

Abstract: In the current study, we sought to compare survival outcomes after breast-conserving therapy (BCT) or mastectomy alone in patients with stage I-IIA breast cancer, whose tumors are typically suitable for both locoregional treatments. The study cohort consisted of 1360 patients with stage I-IIA (T1–2N0 or T0–1N1) breast cancer diagnosed between 2001 and 2013 and treated with either BCT (n = 1021, 75.1%) or mastectomy alone (n = 339, 24.9%). Median follow-ups for disease-free survival (DFS) and overall survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Several studies have supported that breast-conserving therapy may be superior to mastectomy in regard to survival 1–9,17–23 . Compared with BCT, mastectomies inherently carry a host of risks including higher rates of skin flap necrosis, postoperative hematoma, lymphedema, and nerve injury 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have supported that breast-conserving therapy may be superior to mastectomy in regard to survival 1–9,17–23 . Compared with BCT, mastectomies inherently carry a host of risks including higher rates of skin flap necrosis, postoperative hematoma, lymphedema, and nerve injury 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have supported that breast-conserving therapy may be superior to mastectomy in regard to survival. [1][2][3][4][5][6][7][8][9][17][18][19][20][21][22][23] Compared with BCT, mastectomies inherently carry a host of risks including higher rates of skin flap necrosis, postoperative hematoma, lymphedema, and nerve injury. 24 Moreover, mastectomies lead to a healthcare burden requiring hospital stays, increased pain, and often a need for additional staged procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In subgroup forest plot analysis, we observed that in the area of radiotherapy, BCS plus radiotherapy improved OS in patients receiving radiotherapy, and BCS had a better prognosis for these breast cancer patients.BCS plus radiotherapy (BCT) refers to breast-conserving surgery followed by radiation therapy to eradicate any microscopic residual disease, and the e cacy of BCT has been evaluated in clinical trials over the past decades and, in addition to being cosmetically acceptable, it provides survival rates comparable to total mastectomy, especially in early-stage patients, allowing for additional survival bene ts [9,12,18,23,24] . In a further study, we compared the prognosis of patients who underwent BCT with those who underwent TM, and we found no statistical difference in OS between BCT and TM, but the prognosis of BCT patients was better than that of TM patients who underwent radiotherapy, which may be due to the greater extent of surgery and larger incisions in TM patients, which tend to cause a decrease in immunity and less recovery, but for now, the relationship between surgical trauma, adjuvant therapy and immune response relationship is still unknown [15] .…”
Section: Discussionmentioning
confidence: 99%
“…This disease stems from genetic abnormalities that lead to the production of faulty proteins, culminating in uncontrolled cell proliferation and the formation of breast tumors [ 4 ]. Breast cancer is categorized into various stages based on factors such as tumor size, location, and other parameters, each necessitating tailored treatment modalities [ 5 ]. Accurately predicting survival time is imperative for guiding clinicians in prognosis and devising personalized treatment strategies.…”
Section: Introductionmentioning
confidence: 99%